Exoskeletal devices for hand assistance and rehabilitation : a comprehensive analysis of state-of-the-art technologies - Noronha, Bernardo (2021)
Robots are effective tools for aiding in the restoration of hand function through rehabilitation programs or by providing in-task assistance. To date, a multitude of exoskeletal devices employing distinct technologies have been proposed, making navigating this field a challenging task. To this end, we propose a set of classification criteria to help categorize devices. In this review, a set of 97 publications representing 72 active exoskeletal devices for hand assistance and rehabilitation is analysed. Furthermore, the distribution over the years within each of the criteria is presented. Results show clear trends, such as preferring underactuated devices, electrical transducers with flexible transmission or the more recent uptake of soft technologies. Lastly, the readiness level of hand exoskeleton technology is presented in terms of the whole device and each of the identified sub-classifications. Most of the devices are still in laboratory testing phase, undergoing healthy subject trials or limited clinical trials, with very few having actually reached the market. We hope to provide researchers with a comprehensive analysis of currently employed design choices in hand exoskeletons, highlighting the most developed avenues of research and the latest emerging ones.